The Influence of Indonesian Management in Improving the Effectiveness of Organizational Communication and the Character of the Young Generation in the Digital Era - Ika Febriana; Luhut Manurung; Regita Cahyani br Karo Sekali; Agnes Mika Cristina br Manik; Ayu Triani Hutagalung; Grestin Analia Br Togatorop (Jurnal Ilmiah Pendidikan Holistik (JIPH), 2025)
This literature review investigates the role of Indonesian in organizational communication and its impact on the character development of the younger generation in the digital era. Effective use of Indonesian within the organization is essential to maintain clear communication and reduce misunderstandings among members, thereby increasing productivity and creating a harmonious work environment. In addition, in the digital realm, Indonesian not only functions as a communication tool but also as a marker of cultural identity for the younger generation, which encourages positive character traits such as discipline and responsibility. This study emphasizes the importance of structured language management in an educational environment to instill ethical communication practices and preserve local cultural values. In addition, effective language management within an organization is essential for developing professionalism and increasing collaboration among its members. These findings highlight the dual role of the Indonesian language as a means of communication and character education, as well as the need for organizations and educational institutions to strengthen their application in all forms of communication.